MEDIA PEMBELAJARAN TERPADU BERBASIS IT PELUANG MENINGKATKAN KUALITAS PEMBELAJARAN - Haryanto, Henzi; Supriyono, Supriyono; Rahayuningsih, Sri (Jurnal Visi Ilmu Pendidikan, 2024)
The development of technology at this time is very rapidly growing. Where now learning is centered on students by combining learning with technology. This problem is the background of research related to integrated learning media. Opportunities to improve the quality of learning are not only from the teacher but also from the learning media used. The method used in this research is descriptive. Data collection obtained from interviews with teachers related to the lack of IT utilization in learning. The problem of operating IT to develop learning media is one of the factors for the lack of interactive learning media.   The solution to this problem is for teachers to attend training or socialization on how to develop interactive and innovative learning media. Therefore, learning media combined with IT is an alternative for teachers to develop their abilities, make learning fun, and improve the quality of learning.